Evaluation of tear meniscus dimensions using anterior segment optical coherence tomography in video terminal display workers. - Doguizi, Sibel; Sekeroglu, Mehmet A; Inanc, Merve; Yılmazbas, Pelin (Clinical & Experimental Optometry, 2019)
Background: To evaluate tear meniscus height and tear meniscus area measured by optical coherence tomography (OCT) and to determine the prevalence of dry eye disease in video display terminal (VDT) users.Methods: This was a case-control study performed on VDT users. The case group consisted of 53 subjects who vocationally use VDT more than six hours per day and the control group consisted of 49 subjects who used VDT not more than one hour per day. The pre-vocational and post-vocational tear meniscus height and tear meniscus area measurements were performed twice in one day using OCT. Tear-film break-up time, Schirmer's test, Ocular Surface Disease Index score and corneal staining score measurements were performed in all subjects.Results: The mean age was 38.9 ± 5.5 years in VDT users and 37.8 ± 5.8 years in the control group (p = 0.426). Twenty patients (37.7 per cent) had dry eye disease in VDT users and five patients (10.2 per cent) had dry eye disease in the control group (p = 0.001). The mean tear meniscus height and tear meniscus area values (pre-vocational and post-vocational) were significantly lower in VDT users than in the control group (p < 0.001, p < 0.001, p = 0.024 and p < 0.001, respectively). The Schirmer's test results, Ocular Surface Disease Index scores, corneal staining scores and tear-film break-up time values revealed significant differences between VDT users and control subjects (p = 0.002, p = 0.006, p < 0.001 and p < 0.001, respectively). In addition, significant correlations were demonstrated between Schirmer's test results, Ocular Surface Disease Index scores, corneal staining scores, tear-film break-up time measurements, tear meniscus height results and tear meniscus area values.Conclusion: Tear meniscus evaluation using OCT is an effective, non-invasive and sensitive method for detection of dry eye disease in VDT users.